Characteristics of Emerging Adulthood: Adaptation of the Questionnaire in Russian Culture - V.G. Yerofeyeva (Социальная психология и общество, 2023)
Objective. Translation, adaptation, and psychometric testing of the Russian version of the questionnaire “Inventory of the Dimensions of Emerging Adulthood (IDEA)” by A. Reifman, J.J. Arnett and M.J. Colwell on a Russian sample. Background. All over the world, the phenomenon of delayed maturation is acknowledged: young people describe the third decade of their lives as a time of “role without role” and unlimited freedom. In Russia, researchers also note that objective criteria of adult life have been replaced by subjective ones. However, as studies on the adaptation of the questionnaire show, the characteristics of emerging adulthood manifest themselves differently depending on the country and type of culture, so it is necessary to check what aspects of the construct are appropriate in Russia. Study design. A standard psychometric procedure for adapting was carried out. The questionnaire was translated in accordance with international requirements. Next, the original version was checked, it did not fit the Russian sample well. After that, exploratory factor analysis and confirmatory factor analysis were carried out to find a suitable model and check the structural validity of the questionnaire. Reliability indicators were calculated for the resulting model. Participants. The respondents were 676 students aged 18 to 29 living in Russian large cities and millionaire cities. Measurements. “Inventory of the Dimensions of Emerging Adulthood (IDEA)”. Correlation analysis, exploratory factor analysis, confirmatory factor analysis, and assessment of the reliability of the obtained model were carried out. The data were analyzed using the RStudio program. Results. A 5-factor correlation model is proposed that confirms the theoretically distinguished characteristics of emerging adulthood. But the original structure has changed: the questionnaire has been reduced from 31 items and six scales to 19 items and five scales, two items were included in other factors. Conclusions. In Russia, maturation is predominantly associated with the search for identity, experiments, and self-orientation, and to a lesser extent with instability, which can be explained by a mixed type of culture. The questionnaire can be used for research purposes to further test the findings.